Psychosomatic or allergic symptoms?: high levels for somatization in patients with drug intolerance - Hassel, Jessica C.; Danner, Daniel; Hassel, Alexander J. (The journal of dermatology, 2011)
Patients with dermatological diseases often have associated psychological problems. For patients with allergic diseases, only a few publications have focused on psychological aspects. The objective of this study was to assess the psychometric profile, including somatization, depression, anxiety and health-related quality of life (HRQoL), of patients suffering from drug intolerance or hymenoptera venom allergies. In a prospective cohort study design, patients who were admitted to hospital for a challenge test for an alternative drug (n = 49, 24.5% men) or for induction of desensitization therapy with hymenoptera venom (n = 58, 37.9% men) were included. Psychometric screening questionnaires focusing on somatization (Symptom Check List), depression and anxiety (Hospital Anxiety Depression Scale), and also on HRQoL (Short Form questionnaire) were assessed. The scores were compared with population scores and between the two groups. Both groups had significantly higher somatization scores (P ≤ 0.003) than the normal population, and the challenge-test group had lower HRQoL than the normal population. Between-group analysis revealed significantly higher somatization scores in the challenge-test group (P = 0.011) and more impaired HRQoL (physical health domain P < 0.001). Anxiety/depression scores were not significantly different from those of the normal population, or between groups, although abnormally high scores for anxiety were frequent (18% and 12% for the challenge-test and allergy groups, respectively). Somatization, reduced HRQoL and anxiety seem to be part of the symptoms of patients with allergic diseases, especially for patients with drug intolerance. Standardized questionnaires could help to discover patients who may need psychological support. This may help to improve the patients’ symptoms and quality of life.
Gesehen am 07.09.2022